TECHNOLOGY-DRIVEN TEACHER PROFESSIONALISM: A SYSTEMATIC REVIEW OF DIGITAL SKILLS AND EDUCATOR SUSTAINABILITY - Hasmah; Ulin Naini; Hasdiana (International Journal of Teaching and Learning, 2026)
This study aims to analyze technology-driven teacher professionalism by systematically reviewing digital skills and educator sustainability in the post-pandemic era. The rapid advancement of educational technology and the acceleration of digital learning have transformed teachers’ professional roles, requiring educators to possess not only pedagogical competence but also strong digital literacy, technological adaptability, and resilience in technology-enhanced learning environments. This study employs a qualitative approach using the library research method by reviewing scholarly articles, academic books, and institutional reports published between 2020 and 2025. The data were analyzed using descriptive-analytical and thematic analysis techniques to identify trends, challenges, and conceptual developments related to teacher professionalism in the digital era. The findings reveal that digital competence significantly influences teachers’ ability to implement innovative and student-centered learning. Technologies such as learning management systems, artificial intelligence, and online collaboration tools enhance instructional effectiveness and professional connectivity. However, the study also identifies major challenges, including technological inequality, workload intensification, digital fatigue, and declining educator well-being. The findings further demonstrate that sustainable teacher professionalism requires balancing technological innovation with emotional resilience, institutional support, and continuous professional development. This study contributes theoretically by integrating Digital Competence Theory, Teacher Professionalism Theory, and Educator Sustainability Theory into a comprehensive framework. In practice, the study provides recommendations for policymakers and educational institutions to strengthen digital training, technological infrastructure, and teacher well-being programs to support sustainable educational transformation in the digital age.